The Influence of Work environment and Fulfillment of Occupational Needs on The Performance of Geography Teachers at Public Senior High School in Lumajang Regency - Mohamad Na'im; Vionita Firdausy (Future Science, 2022)
The objectives of this study are to analyze the effect of the work environment on the performance of Geography teachers at the state senior high schools in Lumajang Regency, investigate the effect of the fulfillment of occupational needs on the performance of Geography teachers, and analyze the influence of the work environment and the fulfillment of occupational needs on the performance of Geography Teachers. This research deployed quantitative research, coupled with correlational analysis to examine the cause-effect relationship between the dependent and independent variables. Research results point out that the teacher's work environment affects their performance by 30.25%. The fulfillment of occupational needs poses an effect on teachers’ performance by 26.41%. This means that greater fulfillment of occupational needs results in increased teacher performance. Finally, the work environment and the fulfillment of occupational needs concurrently pose a positive effect on the teacher’s performance. The coefficient of simultaneous determination (R2) is 46.9%.